PENGARUH INOVASI PRODUK DAN KUALITAS PELAYANAN TERHADAP MINAT BELI ULANG PADA PRODUK MINUMAN CHATIME DI KOTA GIANYAR - Ni Putu Laras Saraswati; I Gusti Ngurah Agung Gede Eka Teja Kusuma; I Wayan Gede Antok Setiawan Jodi (VALUES, 2022)
Repurchase interest is purchase interest based on past purchase experiences. The purposes of this study are 1. To determine the effect of product innovation on repurchase interest in Chatime beverage products in Gianyar City. 2.To determine the effect of service quality on repurchase interest in Chatime beverage products in Gianyar City. The object of this research is the effect of product innovation and service quality on repurchase interest in Chatime beverage products in Gianyar City. The number of samples used were 155 respondents taken from the people of Gianyar City who had bought Chatime beverage products. Methods of data collection using a questionnaire and data analysis using multiple linear regression analysis technique. The results showed that it was valid and reliable and there was no deviation from the classical assumptions. Product innovation has a positive and significant effect on repurchase interest in Chatime beverage products in Gianyar City. Service quality has a positive and significant effect on repurchase interest in Chatime beverage products in Gianyar City.